PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DI INDUSTRI PERBANKAN INDONESIA - Ririn Setyawati, 08.05.52.0087; Sri mindarti, Ceacilia (Students Journal of Accounting and Banking, 2012)
The purpose of this study was to examine the effect of the implementation of corporate governance measured by board size, proportion of independent board, audit committee existence and size of the companys toward earnings management measures of discretionary accruals calculated using the model Modified Jones Model (Dechow et al 1995 ).The sample in this study is a company engaged in banking that has gone public on the Stock Exchange in the year 2007-2010. Data collection methods in this study using purposive sampling. The amount of observational data obtained in this study as much as 96 observational data from 24 sample banking firms each year.By using a multiple linear regression analysis, the results show that good corporate governance mechanisms are shown to affect the size of the board to reduce the earning management. The result of this research mean that the mechanism by which the company has managed to minimize the practice of earnings management, so that it can be concluded that the mechanism of corporate governance have worked effectively to improve company performance.Keywords: corporate governance, board of directors, auditÂ  ommittees, earnings management